Employment Security and Job Loss: Lessons from Canada's National Railways, 1956-1995 - Ehrlich, Leslie; Russell, Bob (Labour/Le Travailleur, 2003)
Abstract Trade unions have dealt with the thorny issue of layoffs since their formation, but relatively little has been written on the topic of union strategies for surviving large-scale redundancies. This paper examines these strategies in an industry that is all too familiar with massive layoffs: railroading. An analysis of union responses to job losses presupposes an understanding of the factors underlying managerial decisions about staff reduction. We argue that the nature of "downsizing" has changed considerably in the last 40 years. In industries such as railroading, managers were formerly preoccupied with labour-saving technology. As such, unions struggled for a significant voice and co-determinative role in the introduction of new machinery. In Canada, unions came close to obtaining such a role through die recommendations of the Freedman Report. Following their defeat in acquiring a major role in determining issues of technological change, railway unions focused on winning employment security provisions in their contracts. However, managers would view employment security as an anomaly when they turned to organizational change to increase productivity. More recently, older railway unions and newer union entrants to the industry have experienced tactical disagreements over how to confront the offensive against employment security in railroading.